Three in one” – a Collaborative Action Research - Perera, M.E.S. (My University, 2010)
The assumption in Sri Lanka is that equal opportunities to learn English can be provided simply by using the same learning materials, based on the same teaching approach with all the students. Although this assumption has been challenged and the need for more classroom based ethnographic research to ease this problem has been emphasized, there is a paucity of such research.